ChemInform Abstract: [3 + 2] Redox‐Neutral Cycloaddition of Nitrocyclopropanes with Styrenes by Visible‐Light Photocatalysis. Issue 46 (November 2015) - Wang, Chengfeng; Ren, Xiang; Xie, Hujun; Lu, Zhan
Abstract 2‐Alkyl‐2‐nitrocyclopropane‐1‐carboxylates are transformed according to the scalable title reaction with various 1, 1‐methylaryl and 1, 1‐methylalkyl substituted alkenes to form cyclopentane derivatives containing three stereocenters, the two quaternary one of which are formed with excellent diastereoselectivity.